Pemahaman Umat Katolik tentang Kewajiban Kaum Awam dalam Pelaksanaan Tugas Prodiakon - Yuliana Mbura (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2023)
The research aims to determine the understanding of Catholics regarding the obligations of lay people in the task of consecration through the implementation of prodiakon (minister extraordinarius) duties at Paroki Santo Paulus Kaubun. The research was conducted at Paroki Santo Paulus Kaubun, East Kutai from January 2023 to March 2023. The type of research used in this research was qualitative research. Informants in this research were determined using the snowball sampling method, namely looking for informants who knew and were willing to provide information. The data collection technique used was in-depth interviews. The data collected was then analysed through the stages of data reduction, data presentation, and drawing conclusions. The results of this research conclude that the parishioners at Paroki Santo Paulus Kaubun understand that the task of prodiakon is a noble task. Through the prodiakon service, there is a form of involvement of the laity in their mission which is received through the general priesthood and is a noble task.